Manovacuometry as a predictor of extubation success - Tavares , Armando Jarib Gonçalves; Santana , Blenda Alves; Silva , Maisa Adriele Nalves da; Souto , Paulla Romyna de Oliveira; Rodrigues , Elizângela Sofia Ribeiro; Neto , Agrinazio Geraldo Nascimento; Reis , Geovane Rossone; Almeida, Thais Bezerra de (Seven Editora, 2024)
INTRODUCTION: In the Intensive Care Unit (ICU), patients in serious or risk condition, potentially recoverable, who require uninterrupted care, are submitted. Invasive mechanical ventilation (MV) is one of the therapeutic pillars for the treatment of critically ill patients, especially those with respiratory failure. The measurement of respiratory muscle strength is performed with the use of a manometer, this equipment is appropriate for measuring positive pressures (manometer) and negative pressures (vacuometer), consequently measuring inspiratory (MIP) and expiratory (MEP) muscle strength. In general, MIP above 60 cmH2O can be considered normal, values between 40 and 60 cmH2O may indicate normality unless there is visible weakness of other muscles, and values below 40 cmH2O indicate fatigue or respiratory muscle weakness. METHODOLOGY: This is a systematic literature review, carried out through a bibliographic survey related to the theme Novacuometry as a Predictor of Extubation Success. The inclusion criteria were: articles published from 2010 onwards, theses, dissertations in Portuguese and foreign languages. RESULTS: To start the research, we searched the databases for articles with the descriptors, totaling 72 scientific publications, of which 29 remained from the reading of the title, and they were used only once in the database that first referenced the article as a criterion for selection. After reading the abstracts, 18 remained, which make up this integrative review. DISCUSSIONS: Weaning indices from mechanical ventilation can be used in homogeneous populations, although the accuracy may be lower in these populations than in heterogeneous populations. The evaluation of MIP and MEP as a predictor of success in weaning from mechanical ventilation is a routine procedure. FINAL CONSIDERATIONS: In this study, it was possible to observe that the use of manovacuometry is effective to evaluate the strength of the respiratory muscles through MIP and MEP of each patient, thus promoting an increase in the success rates of extubations. The extubation process without an effective evaluation can lead to an increase in: retubation, length of stay on mechanical ventilation, mortality rate, days of hospitalization and, consequently, an increase in hospital costs. DOI:https://doi.org/10.56238/sevened2024.001-059